Comparative clinical and economic evaluation of two alternative antiviral therapy regimens for influenza patients - I. I. Tokin; V. V. Tsvetkov; G. S. Golobokov (Журнал инфектологии)
In the Russian Federation, the number of new cases of influenzaand SARS each year reaches 30 million people, and the annual total  economic damage is estimated at 40 billion rubles, accounting for  about 80% of the damage from all infectious diseases. Today, one of  the main priorities of confronting the consequences of the annual  epidemics of influenza is the development and introduction into  clinical practice of new drugs with proven effectiveness and safety, the use of which is economically feasible.Objective. Conduct a clinical and economic analysis of two  alternative regimens for treating influenza patients using the modern drug Triasavirin® and the known Tamiflu® neuraminidase inhibitor.Materials and methods. The study included 127 patients with a  laboratory confirmed diagnosis of «influenza». All patients were  divided into two groups. The main group consisted of 82 patients  who received Triazavirin® 1 capsule (250 mg) 3 times a day for 5  days. The comparison group consisted of 45 patients who received  Tamiflu® 1 capsule (75 mg) 2 times a day for 5 days. To conduct a  clinical and economic evaluation of two alternative treatment  regimens, cost-effectiveness factors were calculated, such as the  ratio of the cost of therapy to the indicator of its effectiveness. The analyzed events were: (1) recovery by the 5th day from the start of treatment; (2) temperature normalization by the 5th day from the start of treatment; (3) no symptoms of intoxication (headache, myalgia, pain / rei in the eyeballs) by the 5th day from the start of treatment; (4) absence of catarrhal  manifestations (pain / sore throat, cough) to the 10th day from the beginning of treatment.Results. The use of the drug Triazavirin® for treatment of influenza  patients in comparison with the inhibitor of neuraminidase with  Tamiflu® is economically viable, both with respect to the timing of  recovery (cost-effectiveness ratio: 935,57 rubles / unit vs 1859,39  rubles / unit) and normalization of temperature body (cost- effectiveness ratio: 869,53 rubles / unit vs. 2014,33 rubles / unit),  and with respect to the duration of intoxication (cost-effectiveness  ratio: 859,42 rubles / unit vs. 1473,90 rub ./unit) and catarrhal  (coefficient of expenditure e ciency: 869,53 rubles / unit against  1611,47 rubles / unit) syndromes.Conclusion. Triazavirin® is a new effective antiviral agent for the  treatment of influenza. The use of Triazavirin® in the treatment of  patients with influenza is economically viable, due to significant  budget savings both in terms of the cost of treatment, and the  reduction in concomitant therapy and the reduction in the period of  temporary disability of working patients.